No change in Atlantic Yellow-nosed Albatross (Thalassarche chlororhynchos) egg size over 160 years. (2nd April 2020) - Bond, Alexander L.; McClelland, Gregory T.W.; Cuthbert, Richard J.; Glass, Trevor; Repetto, Julian; Ryan, Peter G.
ABSTRACT: Biotic and abiotic conditions in the world's oceans have changed considerably in the last two centuries as a result of anthropogenic factors, including whaling, sealing, fishing, and climate change. For species that have limited variation in life-history traits, life-history characteristics may impede the ability to adapt to changing environmental conditions. Albatrosses are one such group, where breeding investment is limited to a single egg every one or two years. At a coarse level, individuals may decide whether to breed or not, or whether to incubate an egg or not, but one of the only finer-scale adjustment in parental investment involves altering egg size, along with parental foraging and chick provisioning. We investigated changes in egg size in Atlantic Yellow-nosed Albatrosses ( Thalassarche chlororhynchos ) breeding at Tristan da Cunha, South Atlantic Ocean, from 1856 to 2015. We found no change in egg length, or breadth, which may suggest that with regards to this life-history parameter, Atlantic Yellow-nosed Albatrosses appear to have been able to buffer the effects of the trophic, climatic and oceanographic changes in the South Atlantic Ocean.